The concrete non concrete dance of the Guarani Woman (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article dances with the xondaro to reflect on the sensory bodies activated in dance. We dive into dreams and visions to highlight modes of sociality activated between humans and non-humans. The dialogue between process philosophy and the practices danced at Casa de Rezo brings up the notions of transindividuality and non-sensed perception, concepts relevant to compose the rhythmic spirals that sustain this dance. The xondaro becomes free, runs away from words, makes a body out of the body that moves. What does xondaro dance? This is the question that this text proposes to answer.
Keywords: Xondaro; indigenous dance; process philosophy; non-sensual perception; Guarani sociality